1972
DOI: 10.1161/01.str.3.5.527
|View full text |Cite
|
Sign up to set email alerts
|

Arteriographically Visualized Extravasation in Hypertensive Intracerebral Hemorrhage

Abstract: Seven cases are reported in which extravasation of contrast medium from the lateral lenticulostriate artery was observed on cerebral angiography performed in the early stage of hypertensive intracerebral hemorrhage. We advance the theory that continuous bleeding from the ruptured artery with mechanical destruction and displacement of cerebral tissue is the cause of massive hematoma formation, and discuss the possibility of surgical treatment of the acute stage of hypertensive intracerebral hemorrhage. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 9 publications
0
21
1
Order By: Relevance
“…23,24 CT densitometry has been used in the assessment of intracerebral hematoma appearance in the setting of low hematocrit and thrombocytopenia 25 and in the prediction of hemorrhage following tPA administration in acute ischemic stroke. 26 The dynamic expansion of ICH was recognized in the pre-CT era, 27 and subsequently, by using CT, was shown to be maximal in the first few hours following symptom onset. 28 A primary hemorrhagic insult to the brain occurs at ictus with fresh, hypoattenuated liquid blood rapidly clotting to appear hyperattenuated on CT. 29 Larger bleeds have been shown to be more heterogeneous in attenuation at baseline CT. 14 Kim et al 11 found that a low-attenuation "swirl sign" within hematomas on noncontrast CT was associated with increased mortality on univariate but not multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 CT densitometry has been used in the assessment of intracerebral hematoma appearance in the setting of low hematocrit and thrombocytopenia 25 and in the prediction of hemorrhage following tPA administration in acute ischemic stroke. 26 The dynamic expansion of ICH was recognized in the pre-CT era, 27 and subsequently, by using CT, was shown to be maximal in the first few hours following symptom onset. 28 A primary hemorrhagic insult to the brain occurs at ictus with fresh, hypoattenuated liquid blood rapidly clotting to appear hyperattenuated on CT. 29 Larger bleeds have been shown to be more heterogeneous in attenuation at baseline CT. 14 Kim et al 11 found that a low-attenuation "swirl sign" within hematomas on noncontrast CT was associated with increased mortality on univariate but not multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts were made to keep the systolic blood pressure below 150 mm Hg by giving calcium channel blockers. The amount of daily alcohol consumption was calculated with the following formula: the volume (cm 3 ) of drink multiplied by the alcohol concentration (g/cm 3 ) of the drink. The time of onset and the patient's medical history, including alcohol intake, were ascertained by interviewing the patient or the patient's family.…”
Section: Data Collectionmentioning
confidence: 99%
“…A n enlargement of a hematoma (hematoma growth) occurs not uncommonly in patients with spontaneous intracerebral hemorrhage (ICH) after their hospitalization [1][2][3][4][5][6][7][8][9][10][11][12][13] and worsens their clinical outcome. [11][12][13] In our previous review 12 of 419 patients with ICH, we estimated the incidence of hematoma growth (14.3%) and noted the presence of predictors of hematoma growth (viz, a short time interval between admission and onset, an irregularly shaped and large hematoma revealed by an initial CT scan, and liver dysfunction associated with chronic alcohol consumption).…”
mentioning
confidence: 99%
“…15,10,14,16,17) The most important predictor of rapid hematoma expansion is the time after the ic tus, followed by liver dysfunction, low serum fibrinogen level, and hematoma shape. 2,5,6,9,16) Clinical control of blood pressure is important in patients with ICH, because high blood pressure en hances and aggravates bleeding.…”
Section: Introductionmentioning
confidence: 99%